Metabolic response to feeding in Tupinambis merianae: Circadian rhythm and a possible respiratory constraint - Klein, Wilfried; Perry, Steven F.; Abe, Augusto Shinya [UNESP]; Andrade, Denis V. (Univ Chicago Press, 2006)
The diurnal tegu lizard Tupinambis merianae exhibits a marked circadian variation in metabolism that is characterized by the significant increase in metabolism during part of the day. These increases in metabolic rate, found in the fasting animal, are absent during the first 2 d after meal ingestion but reappear subsequently, and the daily increase in metabolic rate is added to the increase in metabolic rate caused by digestion. During the first 2 d after feeding, priority is given to digestion, while on the third and following days, the metabolic demands are clearly added to each other. This response seems to be a regulated response of the animal, which becomes less active after food ingestion, rather than an inability of the respiratory system to support simultaneous demands at the beginning of digestion. The body cavity of Tupinambis is divided into two compartments by a posthepatic septum (PHS). Animals that had their PHS surgically removed showed no significant alteration in the postprandial metabolic response compared to tegus with intact PHS. The maximal metabolic increment during digestion, the relative cost of meal digestion, and the duration of the process were virtually unaffected by the removal of the PHS.